The place for dementia‐friendly communities in England and its relationship with epidemiological need. (24th September 2018) - Woodward, Michael; Arthur, Antony; Darlington, Nicole; Buckner, Stefanie; Killett, Anne; Thurman, John; Buswell, Marina; Lafortune, Louise; Mathie, Elspeth; Mayrhofer, Andrea; Goodman, Claire
Abstract : Objectives: The dementia‐friendly community (DFC) initiative was set up to enable people living with dementia to remain active, engaged, and valued members of society. Dementia prevalence varies nationally and is strongly associated with the age and sex distribution of the population and level of social deprivation. As part of a wider project to evaluate DFCs, we examined whether there is a relationship between provision of DFCs and epidemiological need. Methods: Dementia‐friendly communities were identified through the formal recognition process of DFC status by the Alzheimer's Society and mapped against areas defined by English Clinical Commissioning Groups. We tested whether provision of a DFC was associated with: (1) dementia prevalence, (2) number of known cases, and (3) known plus estimated number of unknown cases. Results: Of the 209 English Clinical Commissioning Group areas, 115 had at least one DFC. The presence of a DFC was significantly associated with number of known dementia cases (mean difference = 577; 95% CI, 249 to 905; P = 0.001) and unknown dementia cases (mean difference = 881; 95% CI, 349 to 1413; P = 0.001) but not prevalence (mean difference = 0.03; 95% CI, −0.09 to 0.16; P = 0.61). This remains true when controlling for potential confounding variables. Conclusions: Our findings suggest that DFC provision is consistent with epidemiological‐based need. Dementia‐friendly communities are located in areas where they can have the greatest impact. A retrospective understanding of how DFCs have developed in England can inform how equivalent international initiatives might be designed and implemented.